1999
DOI: 10.1002/lt.500050514
|View full text |Cite
|
Sign up to set email alerts
|

Successful withdrawal of prednisone after adult liver transplantation for autoimmune hepatitis

Abstract: Corticosteroid withdrawal after orthotopic liver transplantation (OLT) represents an attractive therapeutic option for ameliorating post-OLT metabolic complications, although several reports suggest patients who undergo transplantation for autoimmune hepatitis (AIH) may have a greater incidence of acute and chronic rejection when withdrawn from corticosteroid therapy. The aim of this study is to evaluate the success of corticosteroid withdrawal in patients with AIH after OLT. Twenty-six patients underwent succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 23 publications
0
53
0
Order By: Relevance
“…15 It was shown that 25% of patients progress to chronic hepatitis and cirrhosis within 5 years of transplantation. 16 A recent study from the United Network for Organ Sharing liver transplant database reported that the rate and severity of HCV recurrence, as well as patient and graft survival rates, were similar in patients administered CsA or tacrolimus maintenance therapy. Because of concerns related to steroid promotion of viral replication, discontinuation of steroid therapy in patients undergoing transplantation for HBV and HCV is recommended.…”
Section: Specific Patient Issues Viral Hepatitismentioning
confidence: 99%
“…15 It was shown that 25% of patients progress to chronic hepatitis and cirrhosis within 5 years of transplantation. 16 A recent study from the United Network for Organ Sharing liver transplant database reported that the rate and severity of HCV recurrence, as well as patient and graft survival rates, were similar in patients administered CsA or tacrolimus maintenance therapy. Because of concerns related to steroid promotion of viral replication, discontinuation of steroid therapy in patients undergoing transplantation for HBV and HCV is recommended.…”
Section: Specific Patient Issues Viral Hepatitismentioning
confidence: 99%
“…However, several trials have shown success in withdrawing steroid therapy at short time intervals after OLT. [14][15][16] Previous attempts at complete steroid abstinence in OLT have had mixed results, with a significant number of patients subsequently requiring steroid treatment for rejection. [5][6][7][8] Tisone et al 6 randomized 45 patients to the administration of cyclosporine and azathioprine with or without steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge in each of these areas is particularly important because ideal immunosuppressive regimens after transplantation are being defined that emphasize early reduction in corticosteroid therapy and its ultimate withdrawal. 15,18 This report assesses the frequency, risk factors, and consequences of recurrent autoimmune hepatitis after liver transplantation in patients who have been systematically followed, evaluated by liver biopsy examinations at predefined intervals, and managed with similar immunosuppressive regimens. Diagnostic criteria, based on those codified by an international panel, are applied to all cases to ensure consistent and accurate diagnoses.…”
mentioning
confidence: 99%
“…8 However, findings in various centers have been discrepant regarding the prevalence of recurrence, its consequences, and its risk factors. The importance of HLA-DR3 mismatching between donor and recipient 3,5,6,11,12,13 and the impact of corticosteroid withdrawal on the recurrence of autoimmune hepatitis 5,9,14,18 are now disputed. Optimal results after transplantation require clarification of factors contributing to recurrence and better understanding of the frequency and consequences of recurrent disease.…”
mentioning
confidence: 99%